Early Detection of Hypertension Symptoms in Pregnancy - Fitriani; Sukri; Suradi Efendi; Nour Sriyanah (PT Inovasi Pratama Internasional, 2022)
Hypertension in pregnant women occurs in about 10% of pregnancies worldwide and is one of the main causes of morbidity and mortality in mothers and their babies. The incidence of hypertension during pregnancy can be triggered by stress experienced by the mother, stress is a condition or condition of the body that is disturbed due to psychological pressure or psychological disease, the age of pregnant women if less than 20 years or more than 35 years can also increase the risk of hypertension. Various kinds of risk factors that cause preeclampsia, one of which is a history of hypertension and nutritional status of pregnant women, pregnant women with a history of hypertension will have a greater risk of experiencing preeclampsia. The counseling method was in the form of direct presentation of lecture material and measurement of blood pressure in pregnant women, amounting to 27 people . Submission of material on early detection of symptoms of hypertension in pregnant women with the effectiveness of the counseling pregnant women can gain knowledge about early detection of symptoms of hypertension in pregnant women.